The Representation of Muslim Women with Islamic Dresses in Chinese and Philippine Online Newspapers : a critical discourse analysis - Arvitiarini, Selvira (2015)
This study entitled Representation of Muslim Women with Islamic Dresses in Chinese and Philippine Online Newspapers (A Critical Discourse Analysis) investigates the way Muslim women are represented in Chinese and Philippine online newspapers and the ideologies underlying such representations. Five articles from Chinese online newspapers and six articles from Philippine online newspapers were purposively taken as the data of analysis. This study employs a qualitative method by applying Fairclough's Critical Discourse Analysis (CDA) and Hallidayan Systemic Functional Grammar (SFG) as the tool of analysis. Findings indicate that Chinese online newspaper (Xinhua.net,Sina.com, and Chinapost.com) represent the Chinese government as the one who have a significant control in deciding the way Uighur Muslim women should dress in public places. In addition, Chinese media represents veiled Muslim women particularly veiled Uighur Muslim women related to the act of terrorism and separatism which can harm the unity of the country. On the other hand, Philippine online newspapers (Philippine Daily Inquirer, Inquirer.net and Philstar.com) represent Muslim Philippine women as the people who still have an opportunity to practice their religion, although Philippine Department of Education asked them to remove their face veils inside the classroom. Penelitian ini berjudulThe Representation of Muslim Women with Islamic Dresses in Chinese and Philippine Online Newspapers (A Critical Discourse Analysis) yang bertujuan untuk mengungkap bagaimana representasi perempuan Muslim dalam surat kabar online yang ada di China dan Filipina. Selain itu penelitian ini juga bertujuan untuk mengungkap ideologi yang mendasari kedua media tersebut.Penelitian ini menggunakan lima artikel yang diambil dari surat kabar online China, dan enam artikel yang diambil dari surat kabar online Filipina. Penelitian ini menggunakan metode kualitatif dengan menerapkan Analisis Wacana Kritis Fairclough, dan Hallidayan Systemic Functional Grammar. Hasil penelitian menunjukan bahwa surat kabar online China (Xinhua, Sina, dan Chinapost) merepresentasikan pemerintah China sebagai pihak yang memiliki kontrol yang besar dalam menentukan bagaimana cara perempuan Muslim (Uighurs) harus berpakaian di tempat umum. Selain itu, media online China juga menghubungkan perempuan Muslim yang berjilbab dengan aksi terorisme dan gerakan separatism yang dapat membahayakan keutuhan negara. Di sisi lain, surat kabar online Filipina (Philippine Daily Inquirer, Inquirer, dan Philstar) menunjukan bahwa perempuan Muslim Filipina masih memiliki kesempatan untuk mempraktikan agama mereka dengan menggunakan jilbab, meskipun Departemen Pendidian Filipina meminta mereka untuk tidak menggunaan cadar di dalam kelas.